120k views
4 votes
If p(x) = x2 - 1 and q(x) = 5(x- 1), which expression is equivalent to (p - q)(x)?

1 Answer

4 votes

Answer:
\Large\boxed{x^2-5x+4}

Explanation:

Given function expressions


p(x)=x^2-1


q(x)=5(x-1)

Requirement of the question

Find the expression of
(p-q)(x)


(p-q)(x)=p(x)-q(x)

Substitute values into the given expression


p(x)-q(x)


(x^2-1)-(5(x-1))

Expand the parenthesis


x^2-1-5x+5

Combine like terms


x^2-5x+5-1


\Large\boxed{x^2-5x+4}

Hope this helps!! :)

Please let me know if you have any questions

User Gosfly
by
5.1k points